APAKAH KUALITAS PELAYANAN MEMPENGARUHI KEPUASAN NASABAH? - Kusno, Hendra Sanjaya; Al Qaushar, Muhammad Zihad; Ramli, Ramli; Eviyanti, Novitasari (Buletin Studi Ekonomi; VOLUME.28.NO.02.TAHUN.2023DO - 10.24843/BSE.2023.v28.i02.p03, 2023)
The purpose of this study is to determine the effect of service quality consisting of tangibility, reliability, responsiveness, assurance, and empathy on customer satisfaction simultaneously and partially. The method used is a quantitative method. The population in this study are the customers of the Ronabasa Rural Bank, Balikpapan Head Office. The sample in this study used incidental sampling technique. The population in this study was 1744 customers with a total sample of 94 samples obtained from the slovin formula. The results of hypothesis testing prove that service quality which consists of tangibility, reliability, responsiveness, assurance, and empathy simultaneously affects customer satisfaction. Tangibility partially has a positive and significant effect on customer satisfaction, reliability partially has a positive and significant effect on customer satisfaction, partially responsiveness has no effect on customer satisfaction, assurance partially has a positive and significant effect on customer satisfaction, and empathy partially has a positive and significant effect to customer satisfaction.